Novel Compound Heterozygous PRKN Variants in a Han-Chinese Family with Early-Onset Parkinson’s Disease - Kuan Fan; Pengzhi Hu; Chengyuan Song; Xiong Deng; Jie Wen; Yiming Liu; Hao Deng (Parkinson's Disease)
Genetic factors are thought to play an important role in the pathogenesis of Parkinson’s disease (PD), particularly early-onset PD. The PRKN gene is the primary disease-causing gene for early-onset PD. The details of its functions remain unclear. This study identified novel compound heterozygous variants (p.T240K and p.L272R) of the PRKN gene in a Han-Chinese family with early-onset PD. This finding is helpful in the genetic diagnosis of PD and also the functional research of the PRKN gene.